2020
DOI: 10.7554/elife.59026
|View full text |Cite
|
Sign up to set email alerts
|

Probing the ionotropic activity of glutamate GluD2 receptor in HEK cells with genetically-engineered photopharmacology

Abstract: Glutamate delta (GluD) receptors belong to the ionotropic glutamate receptor family, yet they don't bind glutamate and are considered orphan. Progress in defining the ion channel function of GluDs in neurons has been hindered by a lack of pharmacological tools. Here we used a chemo-genetic approach to engineer specific and photo-reversible pharmacology in GluD2 receptor. We incorporated a cysteine mutation in the cavity located above the putative ion channel pore, for site-specific conjugation with a photoswit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 50 publications
1
23
0
Order By: Relevance
“…Ionotropic activity has also been observed in GluD2 upon activation of G q -coupled metabotropic glutamate receptor with glutamate ( 16 ). The constitutive activity of GluD2 A654T Lurcher mutant and activation via the metabotropic glutamate receptor pathway has been shown to be blocked by a photoactivatable channel blocker attached to a cysteine near the channel pathway, further confirming the two pathways to be mediated by the GluD2 receptor channel ( 17 ). Because the agonist-binding and transmembrane domains of glutamate receptors can function independently, the lack of agonist-induced currents in wild-type delta receptors suggests that conformational changes in the agonist-binding domains cannot be transmitted to the transmembrane segments that form the channel pore.…”
Section: Introductionmentioning
confidence: 84%
“…Ionotropic activity has also been observed in GluD2 upon activation of G q -coupled metabotropic glutamate receptor with glutamate ( 16 ). The constitutive activity of GluD2 A654T Lurcher mutant and activation via the metabotropic glutamate receptor pathway has been shown to be blocked by a photoactivatable channel blocker attached to a cysteine near the channel pathway, further confirming the two pathways to be mediated by the GluD2 receptor channel ( 17 ). Because the agonist-binding and transmembrane domains of glutamate receptors can function independently, the lack of agonist-induced currents in wild-type delta receptors suggests that conformational changes in the agonist-binding domains cannot be transmitted to the transmembrane segments that form the channel pore.…”
Section: Introductionmentioning
confidence: 84%
“…Photoswitchable ligands targeting ionotropic glutamate receptors are not limited to PCLs and PTLs binding to the LBD. A recent study [ 122 ] reported a photoswitchable pore blocker for the glutamate delta2 (GluD2) receptor. Glutamate delta receptors belong to the iGluR family due to their sequence and structure similarity to AMPA, NMDA and kainate receptors.…”
Section: Computational Modeling Of Photoswitchable Ligands Targeting Ligand-gated Ion Channelsmentioning
confidence: 99%
“…However, they are considered to be orphan receptors because their LBD does not bind glutamate; instead, pore opening is regulated indirectly by metabotropic G protein-coupled glutamate receptors. Hence, Lemoine and coworkers [ 122 ] devised a PTL based on a known pore blocker (pentamidine), instead of an agonist binding to the LBD. MAGu ( 21 ) is composed of maleimide, azobenzene and a guanidinium head group that mimics the positively charged groups of pentamidine.…”
Section: Computational Modeling Of Photoswitchable Ligands Targeting Ligand-gated Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, we and others have demonstrated that GluD1 R and GluD2 R channels carry ionic current upon activation of Gα q protein-coupled receptors (GqPCRs), either metabotropic glutamate (mGlu R , Ady et al, 2013; Benamer et al, 2018; Dadak et al, 2017) or α1-adrenergic receptors (Gantz et al, 2020), through a process that involves intact G protein signaling. Intriguingly, in cell lines and brain slices, GluD1 R and GluD2 R channels are open in the presumed absence of agonists and carry tonic cation current (Gantz et al, 2020; Lemoine et al, 2020). The origin of the tonic GluD R current is unknown.…”
Section: Introductionmentioning
confidence: 99%